Table of Content - - (Journal of agricultural, environmental and veterinary sciences, 2024)
Table of Content: 1. Effect of humic supplementation on the germination rate and some morphological characters of three cultivars of sorghum under salt stress conditions Dr. Ghada Mohammed Rashid Al-Taha 2. The Effect of Climate Elements Represented by Temperature, Wind Speed, Relative Humidity and Precipitation on the Production of Organic Barley Harvest in the Kingdom of Bahrain Ms. Huda Fadhalalla Galadari 3. The Forest Heritage of Rosemary in the Taourirt Region - Eastern Morocco - Between Smuggling and Uprooting Dr. Mohammed Lakhdari,Dr. Jaouad El-Bazoui,Dr. Mohamed Aziach, Dr. Abdelouahed Bouberria 4. Evaluating the efficiency of some safe management methods for root-knot nematodes on eggplant in compare with a nematicide, Vaydate Mr. Hafiz Mohamed Dafalla Yousif, Prof. Fahad Abdullah Al-Yahya, Mr. Mostafa Ahmed El-Qurashi 5. Analysis of Al Haydawan (Boerhavia elegana) Seed Extracts: Mineral Composition, Total Phenolic Content, and Primary Antioxidant Activity Ms. Suad Ali Sulaiman Almegairshah, Dr. Asmahan Azhari Ali, Prof. Sahar Hassan Salah Mohamed 6. Compensatory growth in Nubian female goats in Sudan Effect on performance (A) Co-Prof. Yagoub Magboul Yagoub, Prof. Salih Ahmed Babiker